Pediatric Long-term follow up for renal disorders in ALL children by evaluating urine NGAL - Bahoush Mehdiabadi, Gholamreza; Otukesh, Hasan; Hosseini Shamsabadi, Rozita; Emami Arjomand, Mahdie (Journal of Pediatric Nephrology, 2019)
Introduction: Recent Developments in cancer treatment could provide a better survival rate for Acute Lymphoblastic Leukemia (ALL) patients. Survivors faced different long term complication after treatment, for instance cardiac, neurologic and kidney complications. Assessment of the late complications could be useful in the optimization of treatment protocols. The objective of this study was to evaluate the late kidney complications, renal function in ALL patients after therapy. Material & Methods: In this study, we used 46 children. The treatment preformed based on ICBFM protocol. The mean age at the start of the treatment was 53±23 and the mean follow up time was 48±11 months. The tubular damage in these patients was evaluated by urinary NGAL level and the renal function was assessed by GFR. Results: in this study 56.7% of the patients were male. The NGAL level shows abnormally high in 8.9% of patients and the mean urine NGAL was 63±113ng/mL. Also, the mean GFR at the time of the diagnosis and at the time of the start of the follow up were 102.8 ±25.6 mL/min/1.73 m2 and 93.6 ±29.1 mL/min/1.73 m2, respectively. The study indicated GFR were less than 60 mL/min/1.73 m2 in 13.3% of patients. Conclusion: this study indicated the long term follow up of the ALL survivors for kidney disorders are an important manner. The urinary NGAL level shows that 8.9% of the patients are tubular damage by using this treatment protocol. The study concluded that ICBFM protocol is a safe protocol with little long term damage.